Postmenopausal Hyperandrogenism due to Ovarian Hyperthecosis - Laryssa Santos Metzker; Luyanne Azevedo Cabral Ferreira; Julia Caroliny Nogueira Borges; Mariana Furieri Guzzo; Rodrigo Neves Ferreira; Lucas Luciano Rocha Silva; Rodrigo Monico Cavedo; Antonio Chambô Filho (Hindawi Limited, 2023)
Ovarian hyperthecosis or ovarian stromal hyperplasia is a non-neoplastic functional disorder resulting from the presence of luteinized thecal cells within a hyperplastic ovarian stroma. The condition is more common in postmenopausal women than in those of reproductive age and leads to substantial clinical and laboratory alterations, principally androgenetic alopecia, progressive hirsutism, and elevated testosterone levels. Investigation should include clinical evaluation, laboratory tests, and imaging tests to differentiate between the principal diagnostic hypotheses. The gold standard for diagnosis is histopathology of the ovarian tissue. The present case report describes a woman being followed up as an outpatient at the Santa Casa de Misericórdia Hospital in Vitória, Brazil. The objective in publishing this case report is to add to available data on ovarian hyperthecosis, thus contributing towards improving timely diagnosis and treatment. Early diagnosis and treatment would ensure better quality of life for patients with this condition and better physical and mental health. Moreover, these data should be useful both for the medical community and for future research into this disease.